The effect of holding time on the mechanical and physical properties of titania-wollastonite-hydroxyapatite composites - Dinesh R.; Meenaloshini S.; Sankar U. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The effect sintering parameters and various amounts of additives on the TiO2-HA-CaSiO3 composites was investigated this study. TiO2/CaSiO3/HA composites were prepared and characterized by means of physical and mechanical properties. The addition of TiO2 and HA to wollastonite was studied by means of bulk density and Vickers Hardness. The wollastonite composites containing TiO2 (10-30 wt%) and HA (20-40 wt%) were sintered between 1230-1270C, with a ramp rate of 10C/min and a holding time of 1,1.5 and 2 hours. The results indicate that a higher sintering temperature played a significant part in enhancing the physical and mechanical properties as compared to results shown by pure wollastonite, especially for composites containing higher TiO2 (25-30wt%) and lower HA (20-25wt%). BEIESP.